The Critical Importance of Rhodoliths in the Life Cycle Completion of Both Macro- and Microalgae, and as Holobionts for the Establishment and Maintenance of Marine Biodiversity - Fredericq, Suzanne; Krayesky-Self, Sherry; Sauvage, Thomas; Richards, Joseph; Kittle, Ronald; Arakaki, Natalia; Hickerson, Emma; Schmidt, William E. (Frontiers in Marine Science, 2019)
Rhodoliths are the main hard substrata for the attachment of benthic macroalgae in the NW Gulf of Mexico rubble habitats that are associated with salt domes, unique deep bank habitats at ~50-90m depth on the continental shelf offshore Louisiana and Texas. With the advent of additional sequencing technologies, methodologies for biodiversity assessments are now rapidly shifting to DNA metabarcoding, i.e. High Throughput Sequencing (HTS) of environmental DNA mixtures with standardized molecular markers, such as 16S V4, for rapid, cost-effective biodiversity measurement. We newly tested 16S V4 metabarcoding on endolithic portions of mesophtic rhodoliths exhibiting low phototroph colonization that revealed a hidden, cryptic algal diversity targeting spores, propagules, and unsuspected life history stages. We explored cryo-SEM as a potentially more informative method than regular SEM to minimize artefacts of sample preparation in the study of endolithic cell inclusions which brought to light a suite of microalgal stages. We were able to differentiate floridean starch from cellular inclusions. We associated the effect of anatomical growth pattern on presence or absence of cellular inclusions in biogenic rhodoliths. Analyses of combined 16S V4 metabarcodes and 16S Sanger sequences of two red algal orders, the Halymeniales and Bonnemaisoniales, increased the established record of diversity in the region. We view rhodoliths as marine biodiversity hotspots that may function as seedbanks, temporary reservoirs for life history stages of ecologically important eukaryotic microalgae, or as refugia for ecosystem resilience following environmental stress.